Classification and Evaluation of Secondary Posterior Chamber IOL Implantation Scleral Fixation of IOL - Wasif M. Kadri, Zia ul Mazhry (Pakistan Journal of Ophthalmology, 2010)
Purpose: Aim of the study was to evaluate secondary PC IOL implantation in terms of: Variation of surgical procedure required to manage different situations, visual outcome and postoperative complications. Materials and Method: Fifty eyes of 45 patients having traumatic or surgical aphakia were included in the study over the period of 5 years from Oct. 95 to Nov. 2000. The status of posterior capsule varied from intact, partially deficient or totally absent. Similarly the technique varied from simple synechiolysis to anterior vitrectomy combined with simple implantation to single or double haptic trans-scleral fixation. Single piece PC IOL was used in most of the patients while multi piece PC IOL was used very occasionally. No AC IOL was implanted or included for exchange in this series. Postoperative follow up ranged from 6 to 60 months, average being 26.5 months. Results: Surgical technique needed to be varied according to the situation. It ranged from simple implantation on an intact PC (6 eyes), synechiolysis and implantation in 3 eyes, Capsulotomy with anterior vitrectomy and implantation (11 eyes), trans-scleral IOL fixation in 26 eyes and retrieval with fixation of dislocated IOL in 4 eyes. Average visual acuity was in the range of 6/9-6/12. The most common complication was glaucoma (8 cases) followed by vitreous hemorrhage (4 cases with trans-scleral fixation) and hyphaema (2 cases), which resolved in al the patients with no residual complication. Conclusion: Secondary PC IOL implantation is an effective and safe technique for visual rehabilitation of aphakic patients. One should be ready and well versed with the variations of surgical technique required while carrying out such procedures.